Role of 3-oximetabolite phenazepam and levan in realize their neurotropic efficacy - T. A. Voronina; V. B. Larionov; N. Y. Golovenko; L. N. Nerobkova; I. O. Gaidukov (Фармакокинетика и Фармакодинамика, 2014)
Work is devoted to a comparative analysis of the pharmacological action and integral indicators pharmacokinetics of 1,4- benzodiazepine - phenazepam and levan, as well as their total active 3-oximetabolite formed by different mechanisms. It is shown that in the tests levan antagonism corazolum and thiosemicarbazide inferior phenazepam anticonvulsant activity, but surpasses phenazepam on activity in the maximal electroshock test and has a lower severity miorelaxation action. Comparison effects of phenazepam and levad with effects of 3-oximetabolite indicate greater similarity effects than metabolite with phenazepam. With the use of radiolabeled compounds were established change in the ratio of the areas under the concentration curve 3-oximetabolite in the brain and blood when administered phenazepam (AUCbrain / AUCblood = 0,96 ± 0,27) or levan (AUCbrain / AUCblood = 1,4 ± 0,1). This fact is associated with different ways of biotransformation: oxidative hydroxylation of phenazepam CYP450 and nonspecific carboxylesterase hydrolysis of levan, which explains the difference in the pharmacological effect of the test compounds.